1996
DOI: 10.1097/00042560-199612010-00012
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking, Bacterial Pneumonia, and Other Clinical Outcomes in HIV-1 Infection

Abstract: Cigarette smoking has been associated with impaired immune defenses and an increased risk of certain infectious and neoplastic diseases in HIV-1 seronegative populations. We examined the relationship between cigarette smoking and clinical outcome in a prospective cohort of 3221 HIV-1-seropositive men and women enrolled in the Terry Beirn Community Programs for Clinical Research on AIDS. Differences in clinical outcomes between never, former, and current cigarette smokers were assessed using proportional hazard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
100
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(111 citation statements)
references
References 45 publications
8
100
3
Order By: Relevance
“…Although causal interpretation is not warranted, perhaps smoking-related symptoms, such as dizziness, cough, and shortness of breath, are heightened due to immune system vulnerability among HIV patients. Previous research suggests that smoking places patients at increased risk for cognitive (Burns et al, 1996) and lung-related (Miguez-Burbano et al, 2005) problems. By increasing patients' vulnerability to health problems, smoking may further weaken their resistance to infection (Patel et al, 2006), and contribute to an accelerated progression to AIDS (Nieman et al, 1993).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Although causal interpretation is not warranted, perhaps smoking-related symptoms, such as dizziness, cough, and shortness of breath, are heightened due to immune system vulnerability among HIV patients. Previous research suggests that smoking places patients at increased risk for cognitive (Burns et al, 1996) and lung-related (Miguez-Burbano et al, 2005) problems. By increasing patients' vulnerability to health problems, smoking may further weaken their resistance to infection (Patel et al, 2006), and contribute to an accelerated progression to AIDS (Nieman et al, 1993).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Smoking among people with HIV may confer increased risks of medical consequences including development of bacterial pneumonia, cardiovascular disease, emphysema, lung cancer, periodontal disease, oral candidiases, oral hairy leukoplakia, oral lesions, Karposi's sarcoma, and AIDS dementia complex compared to HIV positive non-smokers (Burns et al 1996;Diaz et al 2000;Niaura et al 2000;Palacio et al 1997;Nieman et al 1993;Phelps et al 2001). Smoking is related to increased rates of depression and neurological disease among this HIV positive people, and smoking during pregnancy triples the risk of HIV transmission to the fetus (Niaura et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…1 Among individuals living with human immunodeficiency virus (HIV), studies have found that smokers are at greater risk than nonsmokers to develop bacterial pneumonia, oral lesions and acquired immunodeficiency syndrome (AIDS) dementia complex. [2][3][4] The progression of smoking-induced emphysema is hastened in individuals with HIV infection as well. 5 Increased rates of lung cancer among individuals living with HIV/AIDS appear to be attributed to smoking rather than immunosuppression.…”
Section: Introduction Imentioning
confidence: 99%